A-type stars in the Canada–France Imaging Survey – II. Tracing the height of the disc at large distances with Blue Stragglers. Issue 3 (7th December 2018) - Thomas, Guillaume F; Laporte, Chervin F P; McConnachie, Alan W; Famaey, Benoit; Ibata, Rodrigo; Martin, Nicolas F; Starkenburg, Else; Carlberg, Raymond; Malhan, Khyati; Venn, Kim
ABSTRACT: We present the kinematics of Blue Straggler (BS) stars identified in the Canada–France Imaging Survey (CFIS), covering 4000 deg 2 on the sky in the u band. The BSs sample, characterized through CFIS and Pan-STARRS photometry, has been kinematically decomposed into putative halo and disc populations after cross-matching with Gaia astrometry and SDSS/SEGUE/LAMOST spectroscopy. This decomposition clearly reveals the strong flaring of the outer Milky Way disc. In particular, we show that we can detect this flaring up to a vertical height of | Z | ≃ 8 kpc at a Galactocentric distance of R ∼27 kpc. While some small level of flaring is expected for extended discs built up by radial migration, we demonstrate that the very strong flaring of the Milky Way disc that we observe is likely more consistent with it being dynamically heated by the repeated passage of the Sagittarius dwarf spheroidal galaxy through the mid-plane.